Surgical treatment of acute abdominal complications in hematology patients: outcomes and prognostic factors. Issue 10 (3rd October 2017) - Mokart, Djamel; Penalver, Marion; Chow-Chine, Laurent; Ewald, Jacques; Sannini, Antoine; Brun, Jean Paul; Bisbal, Magali; Lelong, Bernard; Delpero, Jean Robert; Faucher, Marion; Turrini, Olivier
Abstract: The decision to operate on hematology patients with abdominal emergencies can be difficult, as neutropenia and thrombocytopenia are common and the usual causes of abdominal pain are broad. We conducted a retrospective observational study including all hematology patients undergoing emergency abdominal surgery between January 1998 and January 2013. Of the fifty-eight consecutive patients included in the study, nineteen (33%) underwent an operation during the neutropenia period. In the multivariate analysis, a laparotomy after 2002 was protective (HR: 0.05; 95%CI: 0.001–0.24), whereas preoperative septic shock (HR: 8.58; 95%CI: 2.25–32.63) and use of dialysis (HR: 6.67; 95%CI: 2.11–21.07) were independently associated with hospital mortality. Surgery during neutropenia or thrombocytopenia was not associated with prognosis. In hematology patients, emergency abdominal surgery is associated with encouraging hospital survival rates. Surgery should be performed prior to septic shock, regardless of whether neutropenia or thrombocytopenia is present.